Prevalence of taurodontism in premolars - Madeira, M. C. [UNESP]; Faig Leite, H. [UNESP]; Niccoli, W. D. [UNESP]; Simoes, S. [UNESP] (Elsevier, 1986)
Taurodontism does not involve molar teeth exclusively. To call attention to the occurrence of this phenomenon in premolars, 4,459 extracted mandibular and maxillary premolars were examined. Eleven showed evidence of taurodontism. Roentgenograms taken from a buccolingual direction confirmed the diagnosis of taurodont teeth.
Keywords: heredity; human; normal human; normal value; premolar tooth; taurodontism; tooth; tooth malformation; Bicuspid; Brazil; Dental Pulp Cavity; Human; Mandible